2021
DOI: 10.3390/pr9040569
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Synbiotics Conducive to Probiotics Adherence to Intestinal Mucosa Using an In Vitro Caco-2 and HT29-MTX Cell Model

Abstract: The ability of bacteria to adhere to the intestinal mucosa is a critical property necessary for the long-term colonization of the intestinal tract. This ability can be highly sensitive to the presence of prebiotics. However, limited data are available in this respect for beneficial bacteria such as probiotics or resident gut microbiota. We previously demonstrated that the presence of prebiotics may decrease adherence in several pre- and probiotic combinations. Thus, characterizing the interactions between nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…reported that the addition of inulin‐based prebiotics enhanced the adhesion of L . rhamnosus CCDM to Caco‐2 cells, which was speculated to be associated with enhanced negative charge strength of the strain (Krausova et al., 2021). These suggest that 2′‐FL, as an adhesion promoter, might provide an intestinal development advantage for KLDS 8001.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the addition of inulin‐based prebiotics enhanced the adhesion of L . rhamnosus CCDM to Caco‐2 cells, which was speculated to be associated with enhanced negative charge strength of the strain (Krausova et al., 2021). These suggest that 2′‐FL, as an adhesion promoter, might provide an intestinal development advantage for KLDS 8001.…”
Section: Discussionmentioning
confidence: 99%
“…The co-cultures previously proposed in literature for evaluating the mechanism of bacterial adhesion and invasion were obtained by using mucus secreting HT29 subclones which is HT29-MTX to generate a mixed population of enterocytes and mucus secreting cells (Caco-2/HT29-MTX) resembling as closely as possible the intestinal epithelium (Table 2). Bacterial adhesion is influenced by surface characteristics, which are influenced by the structure and composition of the cell wall [1,12]. Krausova et al [1] aimed to identify potentially effective synbiotics by analyzing the adherence of bacterial strains to a Caco-2/HT29-MTX coculture cell line model that mimicking the intestinal epithelium.…”
Section: Co-culture Human Intestinal Model For Adherence and Invasion Studiesmentioning
confidence: 99%
“…Bacterial adhesion is influenced by surface characteristics, which are influenced by the structure and composition of the cell wall [1,12]. Krausova et al [1] aimed to identify potentially effective synbiotics by analyzing the adherence of bacterial strains to a Caco-2/HT29-MTX coculture cell line model that mimicking the intestinal epithelium. They reported high adherence for all strains tested after integrating HT29-MTX cells for mucin synthesis in this model.…”
Section: Co-culture Human Intestinal Model For Adherence and Invasion Studiesmentioning
confidence: 99%
See 2 more Smart Citations